Influence of f-d exchange interaction on the properties of nanoscale structures based on Fe, Co, Ni metals and rem oxides. A review - A. M. Kasumov; A. I. Dmitriev; K. A. Korotko; V. M. Karavaeva; K. O. Vyshnevska; A. I. Ievtushenko (Хімія, фізика та технологія поверхні, 2022)
A review of the works of the authors published in the period 2009–2022 and devoted to the study of the properties of nanosized structures containing contacting layers of Fe, Co, Ni, Fe2O3 / REM (Rare Earth Metal) oxide is carried out. The technology for the creation and structural features of these nanostructures are also considered. Physicochemical phenomena in the interface of contacting layers are very multidisciplinary. This is a consequence of their dependence on various conditions, primarily on the modes of technologies for their production and the properties of the initial components. The problem becomes much more complicated when studying magnetic nanostructures. To study effectively the properties of layered nanostructures containing ferromagnetic films, we used magnetic research methods. Using the EPR method, it has been found that between atoms with unfilled f- and          d-electron sub-shells, which are part of the contacting layers, an f-d exchange interaction occurs, which orders the magnetic structure of the ferromagnetic layers.  Using the method of the anomalous Hall effect, it is shown that the ordering of the magnetic structure leads to an increase in their magnetization. The enhancement of the galvanomagnetic properties in the Fe3O4/REМ оxide/Fe3O4 structures shows that the exchange interaction can have both f-d and d-d character. And this, in turn, leads to an increase in magnetization-dependent properties, such as galvanomagnetic, magneto-optical, and current-voltage properties. This can be used in nanotechnologies to enhance the above properties without energy consumption and the use of amplifying equipment.